Researching Police Transformation: The Ethnographic Imperative - Marks, Monique (The British journal of criminology, 2004)
This paper makes a case for employing an ethnographic approach in trying to understand police organizational transformation. It argues that changing police organizations demands change in the cultural knowledge of the police and that in order to understand this cultural knowledge and assess whether it has changed, it is important for the researcher to immerse herself in the daily organizational field of the police. The paper then explores some of the moral dilemmas and personal difficulties that police ethnographers may encounter, by reviewing my own ethnographic work in South Africa